Employ the 5H Model, Evaluate its Efficacy, And Illustrate the Change in Elderly Depression Levels and Symptoms - Le, Son Quang; Nguyen, Anh Thi Tram (National Journal of Community Medicine, 2024)
Introduction: Age-related disorders include mental health. This reduction in intergenerational cohesion and filial responsibilities has caused older people's dissatisfaction, sadness, and grief. Depression and dementia impair elderly people worldwide by taking away their independence and autonomy. Methodology: The authors use the experimental approach to implement the 5H model, evaluate its efficacy, and show the change in depression levels and symptoms in Quang Ngai's elderly. The author chose 26 senior persons from Truong Quang Trong Ward and 23 from Tinh Thien Village to engage in the intervention study. The semi-experimental study compared N=60 samples (Experimental Group=30 and Control Group=30). The elderly control group receives conventional therapy according to the local program, whereas the experimental group receives community intervention. The GDS-15 and ICD-10 examined the intervention's efficacy. Results: This study found that I mild depression had a significant change post-intervention; (ii) the mean score of depression through 2 assessments (GDS-15 scale and ICD-10 clinical assessment) both showed a significant reduction; (iii) females tended to change more than males; (iv) elderly aged 60-70 were easier to change than those over 80 years old; and (v) community-based psychosocial therapy had a significant impact on depression. Conclusion: Considering the aforementioned favourable results, the Quang Ngai city depression prevention intervention program for the elderly is practical and can reduce symptoms, severity, and reverse depression. Hence, the model is applicable across Quang Ngai City.